1997
DOI: 10.1097/00003246-199701000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous venovenous hemofiltration with dialysis on lactate clearance in critically ill patients

Abstract: Continuous venovenous hemofiltration with dialysis cannot mask lactate overproduction, and its blood concentration remains a reliable marker of tissue oxygenation in patients receiving this renal replacement technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 22 publications
2
59
1
3
Order By: Relevance
“…Some investigators have suggested the lactate removal by CHDF per se. However, it was reported that the blood lactate concentration remains a reliable marker of tissue oxygenation even during CHDF [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have suggested the lactate removal by CHDF per se. However, it was reported that the blood lactate concentration remains a reliable marker of tissue oxygenation even during CHDF [22]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study looked at lactate elimination in 10 patients with acute renal failure who were on continuous venovenous hemodiafiltration. In the absence of lactic acidosis endogenous lactate clearance did not appear to be impaired; however, the filter clearance of lactate accounted for only 2.4% of the overall lactate clearance [9]. There is limited information on the clearance of lactate in the setting of lactic acidosis.…”
Section: Principles Of Acid-base and Electrolytes Management In Crrtmentioning
confidence: 97%
“…In the last 5 years there have been several publications commenting on the beneficial role of bicarbonate as buffer instead of lactate [8][9][10][11][12][13][14][15][16][17][18]. Use of lactate ions as base has been associated with an increase in urea generation [8].…”
Section: Principles Of Acid-base and Electrolytes Management In Crrtmentioning
confidence: 99%
See 1 more Smart Citation
“…Some success has been reported in the treatment of combined renal failure and lactic acidosis with the use of continuous haemofiltration using lactate free dialysate [134]. This treatment does not mask lactate overproduction [135] and, in the face of sustained hyperlactataemia, an underlying diagnosis of fulminant hepatic failure or gangrenous bowel should be considered.…”
Section: Treatment Of Lactic Acidosismentioning
confidence: 99%